2018
DOI: 10.1002/anzf.1307
|View full text |Cite
|
Sign up to set email alerts
|

Toward Father‐friendly Parenting Interventions: A Qualitative Study

Abstract: Levels of father participation in parenting interventions are often very low, yet little is known about the factors which influence father engagement. We aimed to qualitatively explore perceived barriers to, and preferences for, parenting interventions in a community sample of fathers. Forty‐one fathers across nine focus groups were interviewed using a semi‐structured interview. Data were analysed using inductive thematic analysis. Key barriers to father participation identified included: the perception that i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(61 citation statements)
references
References 30 publications
2
48
1
1
Order By: Relevance
“…Most fathers in the current study were not present during the initial recruitment discussion and were subsequently recruited to the study via their partner. Future studies should incorporate father‐direct recruitment strategies to increase opportunities for father participation in research (Goldstein et al, ; Sicouri et al, ; Tully et al, ). This, coupled with a natural shift toward a more shared caregiver role when a child is in hospital (McNeill, ), will likely result in an increased representation of fathers in psychosocial research over the next decade.…”
Section: Discussionmentioning
confidence: 99%
“…Most fathers in the current study were not present during the initial recruitment discussion and were subsequently recruited to the study via their partner. Future studies should incorporate father‐direct recruitment strategies to increase opportunities for father participation in research (Goldstein et al, ; Sicouri et al, ; Tully et al, ). This, coupled with a natural shift toward a more shared caregiver role when a child is in hospital (McNeill, ), will likely result in an increased representation of fathers in psychosocial research over the next decade.…”
Section: Discussionmentioning
confidence: 99%
“…These contemporary programs hold promise for many different types of parents, however this review will highlight three groups historically underserved by face‐to‐face parenting programs: parents of lower socioeconomic position (SEP), families living in rural areas, and male parents. Despite representing populations with distinct needs and barriers to accessing services (Lavigne et al, ; Sicouri et al, ), these groups have been consistently underrepresented within parenting research and among samples selected for the development and piloting of traditional parenting programs (Lundahl, Tollefson, Risser, & Lovejoy, ; McGoron & Ondersma, ). This indicates that presently, Australian parenting programs are designed and implemented without consideration for the specific parenting needs of these groups; and this underrepresentation is reflected in poorer youth mental health outcomes among rural and lower‐SEP populations (Bradley & Corwyn, ; Lawrence et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…It could be related to maternal ‘gatekeeping’ (e.g., [ 16 ]), whereby mothers’ beliefs about the paternal role may influence the level of father involvement in their child’s life. Focus group research with fathers has identified both maternal gatekeeping and stigma around help-seeking as barriers to fathers attending parenting interventions [ 17 ], and these factors may therefore play a key role during the family’s initial point of contact with services. It is also likely that service-level policies, such as offering sessions during work hours only, might not only act as practical barriers to father attendance at sessions, but similarly influence rates of father-instigated referrals.…”
Section: Discussionmentioning
confidence: 99%